Surgical treatment of craniosynostosis in infants: open vs closed repair. Issue 3 (June 2016) - Erb, Thomas O.; Meier, Petra M.
Abstract : Purpose of review: Correction of craniosynostosis may require extensive surgical interventions with related intra and postoperative complications especially hemorrhage. To reduce the intervention's impact and associated complications, less invasive surgical alternatives have evolved. The present review comprehensively summarizes surgical techniques, perioperative anesthesia management, success rates, complications, the results of outcome evaluations, and predictors of intra and postoperative complications. Recent findings: Recent evaluations suggest that less invasive methods represent valuable techniques with comparable cosmetic and volumetric results but reduced overall impact and complications. Furthermore, risk stratification based on predictors might optimize safety and guide decision-making concerning the required level of postoperative clinical care. Summary: Neuroendoscopic techniques, designed to minimize surgical incision, dissection, and blood loss, are becoming efficacious and valuable alternative therapeutic options reducing the need for fluid replacement and invasive hemodynamic monitoring. Since hemorrhage represents the most important complication in open craniosynostosis repair, prevention strategies such as the use of tranexamic acid should be considered. Sufficient correction of entailed coagulopathies is crucial.